2011
DOI: 10.1097/ta.0b013e31821266e0
|View full text |Cite
|
Sign up to set email alerts
|

Pathophysiology of Early Trauma-Induced Coagulopathy: Emerging Evidence for Hemodilution and Coagulation Factor Depletion

Abstract: Background-Trauma patients present with a coagulopathy, termed early trauma induced coagulopathy (ETIC), which is associated with increased mortality. This study investigated hemostatic changes responsible for ETIC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
82
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(90 citation statements)
references
References 15 publications
7
82
0
1
Order By: Relevance
“…An INR-based ATC definition offers advantages over definitions using the PT or PT ratio since (1) INR is directly reported by the laboratory and (2) INR corrects for variability in the prothrombin time ratio over time and between laboratories (52). While we were unable to evaluate definitions employing PTT, platelet count, or fibrinogen level, these parameters alone are insensitive for clinically significant coagulopathy and unlikely to markedly improve an INR-based definition (9, 26, 53-55). Viscoelastic assays' speed, ability to simulate in vivo clotting, and utility for mechanistic studies of acute coagulopathy make them attractive (14), but data linking specific functional abnormalities detected by these tests to trauma outcomes are too limited to base ATC diagnosis on this technology (56-58).…”
Section: Discussionmentioning
confidence: 98%
“…An INR-based ATC definition offers advantages over definitions using the PT or PT ratio since (1) INR is directly reported by the laboratory and (2) INR corrects for variability in the prothrombin time ratio over time and between laboratories (52). While we were unable to evaluate definitions employing PTT, platelet count, or fibrinogen level, these parameters alone are insensitive for clinically significant coagulopathy and unlikely to markedly improve an INR-based definition (9, 26, 53-55). Viscoelastic assays' speed, ability to simulate in vivo clotting, and utility for mechanistic studies of acute coagulopathy make them attractive (14), but data linking specific functional abnormalities detected by these tests to trauma outcomes are too limited to base ATC diagnosis on this technology (56-58).…”
Section: Discussionmentioning
confidence: 98%
“…Activated platelets adhere to damaged tissues and serve as catalysts for amplification of thrombin generation. These processes are reflected in the findings of observational clinical studies that show reduced clotting factor and physiological anticoagulant levels [21][22][23], high thrombin generating capacity [3,4,21,[24][25][26] and reduced platelet counts [27,28] Overall, these data indicate a consumptive coagulopathy. The most depleted coagulation factors are fibrinogen and factor V [22,28], which are likely consumed in part by activated Protein C or free plasmin [29,30], although the relative importance of these proteases in reducing factor levels remains unknown.…”
Section: Pathophysiologymentioning
confidence: 98%
“…Obviously, dilution contributes to coagulopathy in trauma and several studies have shown the close relationship in patients with trauma. 1,61 In the early stage, fluid administration is often small or limited in some countries, 12 thus the critical role of hemodilution in the early stage is questioned.…”
Section: Classic Triad Theorymentioning
confidence: 99%